Role of flavonoids in inhibiting triple-negative breast cancer - Wang, Shuai; Wang, Kuanyu; Li, Cheng; Chen, Jing; Kong, Xiangding (Frontiers in Pharmacology, 2024)
Increasing incidences of metastasis or recurrence (or both) in triple-negative breast cancer (TNBC) are a growing concern worldwide, as these events are intricately linked to higher mortality rates in patients with advanced breast cancer. Flavonoids possess several pharmaceutical advantages with multi-level, multi-target, and coordinated intervention abilities for treating TNBC, making them viable for preventing tumor growth and TNBC metastasis. This review focused on the primary mechanisms by which flavonoids from traditional Chinese medicine extracts inhibit TNBC, including apoptosis, blocking of cell cycle and movement, regulation of extracellular matrix degradation, promotion of anti-angiogenesis, inhibition of aerobic glycolysis, and improvement in tumor microenvironment. This review aims to improve the knowledge of flavonoids as a promising pharmacological intervention for patients with TNBC.